Exchange coupling and single molecule magnetism in redox-active tetraoxolene-bridged dilanthanide complexes. Issue 5 (19th December 2017) - Zhang, Peng; Perfetti, Mauro; Kern, Michal; Hallmen, Philipp P.; Ungur, Liviu; Lenz, Samuel; Ringenberg, Mark R.; Frey, Wolfgang; Stoll, Hermann; Rauhut, Guntram; van Slageren, Joris
Abstract : The magnetic properties of the title complexes were studied by EPR spectroscopy, magnetometry and ab initio calculations. Abstract : Tetraoxolene radical-bridged lanthanide SMM systems were prepared for the first time by reduction of the respective neutral compounds. Magnetic measurements reveal the profound influence of the radical center on magnetic behavior. Strong magnetic couplings are revealed in the radical species, which switch on SMM behavior under zero applied field for Dy III and Tb III compounds. HFEPR spectra unravel the contributions of the magnetic coupling and the magnetic anisotropy. For Gd III this results in much more accurate magnetic coupling parameters with respect to bulk magnetic measurements.